High Frequency of Fusion Gene Transcript Resulting From t(10;11)(p12;q23) Translocation in Pediatric Acute Myeloid Leukemia in Poland - Ksiazek, Teofila; Czogala, Malgorzata; Kaczowka, Przemyslaw; Sadowska, Beata; Pawinska-Wasikowska, Katarzyna; Bik-Multanowski, Mirosław; Sikorska-Fic, Barbara; Matysiak, Michał; Skalska-Sadowska, Jolanta; Wachowiak, Jacek; Rodziewicz-Konarska, Anna; Chybicka, Alicja; et al. (Frontiers in Pediatrics, 2020)
11q23/MLL rearrangements are frequently detected in pediatric acute myeloid leukemia. The analysis of their clinical significance is difficult due to the multitude of translocation fusion partners and their low frequency. The presence of t(10;11)(p12;q23) translocation was previously identified in pediatric AML. It is considered as the second most common translocation detected in pediatric 11q23/MLL-rearranged (present KMT2A) AML, after t(9;11)(p22;q23). The presence of the above translocation was previously identified as an unfavorable prognostic factor. Since June 2015 the Polish Pediatric Leukemia/Lymphoma Study Group has applied the therapeutic protocol requiring extensive diagnostics of genetic changes in pediatric AML. Until November 2019, molecular genetic studies were performed in 195 children with diagnosed AML to identify carriers of fusion gene transcripts for 28 most common chromosomal translocations in acute leukemia. The fusion gene transcript for translocation t(10;11)(p12;q23) involving MLL gene was detected with unexpectedly high frequency (8.9%) in our research. It was the highest frequency of all detected MLL rearrangements as well as other detected fusion gene transcripts from chromosomal aberrations characteristic for AML. It seems that chromosomal aberration between chromosomes 10 and 11 can be relatively frequent in some populations. Paying attention to this fact and ensuring proper genetic diagnosis seem to be important for appropriate allocation of patients to risk groups of pediatric AML treatment protocols.